PERCEPTIONS OF STUDENTS OF FACULTY OF AGRICULTURE AND ANIMAL HUSBANDRY UNIVERSITAS MUHAMMADIYAH MALANG ON THE FUTURE OF FARMERS IN INDONESIA - Chairinina Rizka Fitria; Ary Bakhtiar; Harpowo (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2022)
As a young generation with high potential skills, students play an essential role in shaping the future. However, many of them make it up and undervalue the agricultural sector. In response to these, this study aims to analyze the student perceptions of the future of farmers in Indonesia. The results showed that factors influencing the analysis of student's perception of the farmers have a significant positive relationship, namely between the variables of students’ perception and profession as a farmer. The Product Moment Correlation test showed that the r count (Pearson Correlation) reached 0.667, meaning that the relationship between the two variables was large or strong.